Efficacy and Safety of Carbetocin in Comparison to Oxytocin in the Active Management of Third Stage of Labour Following Vaginal Delivery: An Open Label Randomized Control Trial (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(S):This study was conducted to evaluate the efficacy and safety of carbetocin in comparison to oxytocin in the active management of third stage of labour following vaginal delivery.Methods:A randomized-controlled trial was conducted in the Institute of Child and Mother Health (ICMH), Dhaka, Bangladesh over a period of nine months from January to September, 2015. Patients who got admitted in ICMH with labour pain were assessed by general examination, abdominal examination and labour status was confirmed by per vaginal examination. On the basis of selection criteria total 94 pregnant women who had undergone vaginal delivery were randomized for two groups of drugs. According to computer generated randomization sequential number was allocated for cases. One group of patients received intravenous 100 micro gram carbetocin and another group of patients received intramuscular 10 IU oxytocin in third stage of labour. Outcome measures such as amount of blood loss in 24 hours, primary PPH, massive blood loss, need of fundal massage, need for additional uterotonic therapy, blood transfusions as well as other adverse effects were all documented.Results: In this study, massive blood loss did not occur in any of patients in carbetocin group. But massive blood loss occurred in 8.5% women of oxytocin group. Further fundal massage, immediate blood transfusion and additional uterotonics were not needed by any patient in carbetocin group. In oxytocin group, fundal massage required in 10.6% of women, blood transfusion was needed for 6.4% patients and additional uterotonics was needed for 10.6% women. Average amount of blood loss were 64 ml less in carbetocin group and adverse effects of drugs were almost similar in both groups. Primary PPH was developed 6.4% in oxytocin group but none of patients developed PPH in carbetocin group.Conclusion: Carbetocin appears to be an effective new drug in the active management of third stage of labour in vaginal delivery. A single dose of 100 microgram IV carbetocin is more effective than oxytocin for maintaining adequate uterine tone, less blood loss and preventing postpartum bleeding in women undergoing vaginal delivery. So, carbetocin can be considered as a good alternative to oxytocin in the active management of third stage of labour in vaginal deliveryBangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 3-9